Fast Forwad and Shortcut to Adiabaticity Methods in Two Level System - Apriansyah, Rigo Tambang; Setiawan, Iwan; Koto, Irwan (Kasuari: Physics Education Journal (KPEJ), 2025)
This research examines the fast forwad and shortcut to adiabaticity (STA) method in accelerating adiabatic dynamics applied to two level systems. The fast forwad and shortcut to adiabaticity (STA) method is a strategy developed to accelerate the evolution of quantum systems from the initial state to the final state in a short time. In this method, the acceleration scheme is built by modifying the Hamiltonian through the addition of additional terms to the initial Hamiltonian as regularization terms so that the time-dependent Schrodinger equation is still fulfilled. The formulation of the problem in this study is how to find the regularization term and additional Hamiltonian of the fast forwad and STA methods. The methodology used to obtain regularization terms with adiabatic magnetic field and analysis of wave function solutions and additional Hamiltonians. The results of the study are regularization terms and additional Hamiltonians to shorten the dynamics of the system adiabatically. In the fast forwad method to obtain the regularization term, one energy information of the system is required, while in the STA method all energy information of the system is required